An exploratory analysis of major dropdowns in Student Evaluation of Teaching ratings in higher education - Leguey, Santiago; Cid-Cid, Ana I.; Guede Cid, Rocío; Prieto, Jaime (Multidisciplinary journal of educational research, 2023)
We present an exploratory study of Student Evaluation of Teaching (SET) surveys that focused on analyzing the major dropdowns that sometimes occur in SET scores of those university teachers who teach the same subject for at least two consecutive years. Specifically, the purpose of this study was to identify those SET survey items associated with major dropdowns in teacher evaluations. The sample comprised SET surveys ratings from one Spanish University over five years, for a total of 2,284 different teacher-subject pairs under analysis. The 5% percentile of the differences between the teacher and subject SET ratings in two consecutive years was used as the cut-off point to identify major dropdowns. Frequency tables were used for analysis. The results highlighted SET survey items related to teaching methodology as those most associated with major dropdowns in teachers’ ratings. In particular, the item concerning teachers’ compliance with class schedules showed the highest frequency of occurrence. Beyond the specific scores obtained or the specific items in which major dropdowns may take place, in this study we discuss the importance of incorporating major dropdowns analysis to SET surveys reports in the future.